2003
DOI: 10.1021/ef0300949
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Synthesis of Oxygenates and Higher Hydrocarbons from Methane and Carbon Dioxide Using Cold Plasmas

Abstract: A density functional theory (DFT) study has been conducted in this work to investigate the reaction mechanism of synthesis of oxygenates and higher hydrocarbons from methane (CH 4 ) and carbon dioxide (CO 2 ), using cold plasmas. The main dissociation routes of the reactants were analyzed. The feasibility of the formation of various products, including syngas, higher hydrocarbons, and oxygenates, was discussed. The DFT study confirmed that the major obstacle of the synthesis is the dissociation of the reactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Each step of the second pathway requires a high energy input and has to overcome a high energy barrier. The enthalpy for the combination of CH$ fragments into acetylene was calculated to be À263.6 kcal/mol, close to the value calculated by Wang et al (À265.6 kcal/mol) [42].…”
Section: 4supporting
confidence: 87%
“…Each step of the second pathway requires a high energy input and has to overcome a high energy barrier. The enthalpy for the combination of CH$ fragments into acetylene was calculated to be À263.6 kcal/mol, close to the value calculated by Wang et al (À265.6 kcal/mol) [42].…”
Section: 4supporting
confidence: 87%
“…[8,9] Afew groups have reported on the formation of trace oxygenates (e.g., alcohols and acids) as side products in plasma DRM for syngas production. [10] Thus far, the use of NTPs for the direct conversion of CO 2 and CH 4 into oxygenates has resulted in poor selectivities and yields.…”
mentioning
confidence: 99%
“…The density functional theory study confirmed that the dissociation of CH 4 and CO 2 is the main obstacle. 22 Therefore, it can be explained from the point of [Color figure can be viewed in the online issue, which is available at wileyonlinelibrary.com. ]…”
Section: Resultsmentioning
confidence: 99%